การพัฒนามาตรฐานสากลด้านการอ่าน - พนมวัน ณ อยุธยา ทรงพร; ปิลันธนานนท์ นาตยา (Al-HIKMAH Journal, 2018)
The development of students for being efficient readers in order to have a desirable characteristic as a globally competitive citizen. One of the skills and abilities needs to be developed urgently is their abilities in reading which are the important factors need for a lifelong learning process in the social globalization. The purposes of this research were to 1) Analyze and synthesize a variety of information on reading of International Standards in Reading English Languagein the secondary level 2) The International reading standards development 3) Evaluate the standard of reading developed and study on the international reading standards in schools. The researcher used the method to analyze with the content analysis from the international PISA test of reading literacy, the reading curriculum standards in 4 countries, and the core curriculum of the Basic Education 2551 BE. The results were as follows: the four international reading standards and indicators in the secondary level are rated beneficial to the evaluation based on PISA, the O-NET tests, continuing education and performance in occupation, and a good contribution to daily life reading. International reading standards can be used to set the reading policy and focus on reading. To set the national agenda and strategies on reading. Curriculum development, additional courses and learning units design, instruction, development of media technology and innovation, as well as supplementary books. Development of the reading evaluation in line with international assessments, reading supervision, teachers’ development on reading literacy, to evaluate the reading quality of the matthayomsuksa 3 students before graduation, establishing teaching professional standards, and developing pedagogical curriculum in accordance with reading curriculum at all levels of education.